Conceptual Implementation of a Photonic–Plasmonic Transistor onto a Structured Nano‐Guided Hybrid System. Issue 11 (5th May 2020) - Lio, Giuseppe Emanuele; Madrigal, Josslyn Beltran; Couteau, Christophe; Blaize, Sylvain; Caputo, Roberto
Abstract : The interplay between quantum emitters and plasmonic nanostructures can unlock unprecedented functionalities, potentially useful for novel‐concept photonics. Herein, the design and conceptual implementation of an integrated photonic–plasmonic transistor is reported. A mixed top‐down and bottom‐up nanofabrication approach is used to realize a prototype based on a nano‐guided hybrid system enabling the interaction between gold nanostructures and emitters and thus resulting in a plasmon–exciton exchange. In analogy with a classical transistor (MOSFET), gold nanotapers (NTs) are fabricated in specific positions on a TiO2 waveguide to behave as drain, source, and gate for highly localized electric near‐fields. Photopolymerization by evanescent waves is then exploited to grow a polymeric ridge containing quantum dots directly on top of the NTs. The fluorescent spectroscopy of the prototype evidences a sensitive Purcell enhancement of the emission of the quantum dots located in proximity of the apices of gold NTs. The numerical study of the hybrid system demonstrates how this enhancement is controlled to efficiently route and modulate high‐frequency optical signals in the novel photonic device. Abstract : In the conceptual design of an integrated photonic–plasmonic transistor, quantum emitters and plasmonic nanostructures unlock unprecedented functionalities, potentially useful for novel–concept photonics. A mixed nanofabrication approach allows realizing a prototype where a nano–guided hybrid system enables plasmon–exciton exchanges. The numerical study of the system confirms the possibility to efficiently route and modulate high–frequency optical signals.